EFFICACY OF AYURVEDA FORMULATIONS AND BASTI CHIKITSA ON MUTRAGHATA W.S.R. TO BENIGN PROSTATIC HYPERPLASIA: A REVIEW ON RESEARCHES CONDUCTED AT GUJARAT AYURVED UNIVERSITY, JAMNAGAR - G, Banothe; VD, Mahanta; SK, Gupta; TS, Dudhamal (International Journal of Ayurveda and Pharma Research, 2015)
Benign Prostatic Hyperplasia (BPH) is major geriatric problem of obstructive uropathic disorders described in Ayurveda classic as one type of Mutraghata (urinary disorders). Twelve types of Mutraghata reflect the symptoms of retention, incomplete voiding, dribbling, hesitancy, incontinence of urine, etc. These are basically presented the features related to the Lower Urinary Tract Symptoms (LUTS) and can be co-related with Benign Prostatic Hyperplasia (BPH) in modern parlance. BPH is a non-malignant enlargement of the prostate gland, caused by the excessive growth of prostatic nodules. The overall incidence rate of BPH is about 15 per 1000 men per year. The conservative treatments have been mentioned to relieve the obstructive uropathy by reducing prostate size and enhancing the tone of urinary bladder musculature in contemporary medical science. Similarly in Ayurveda also, various researches are going on to find out a suitable treatment option to manage Mutraghata. In the Sushruta Samhita the choice of treatment for Mutraghata is Uttara Basti as Shodhan Chikitsa. In this review, in most of the studies Matra Basti was given in one group of patients and showed the encouraging results. This review article is attributed to the researches on Mutraghata carried out at I.P.G.T. & R.A., Gujarat Ayurved University, Jamnagar, Gujarat.